Bird Homogenization at regional scale (Umbria, central Italy): a lack of evidence for a change in the 2001-2014 period (Avocetta, 2016)
The decline of stenoecious species and the development of euryoecious species are causing a flattening of communities, which gradually lose their peculiar characteristics ending up being more and more similar among themselves and causing a general loss of biodiversity. Amongst the various causes of this phenomenon, known as ‘functional homogenization’ (FH), lies the urbanization which is responsible for the alteration of semi natural and natural environment. The environmental transformation is also affecting Umbria (a region in the centre of Italy) where in recent years there has been a significant intensification of this phenomenon. The purpose of the study is to verify whether FH is also happening in this region by analyzing the community of breeding birds to a regional level. Starting from a sample of 1,696 bird watching stations covered between 2001 and 2014, using the software TRIM it was possible to analyze the trend of 132 bird species classified as specialists and generalists in terms of habitat-selection. Furthermore, for each year taken into account it has been calculated the value of Community Specialization Index (CSI – Filippi-Codaccioni et al., 2010), an indicator of the importance of specialist species within the whole regional bird community. Finally, it was considered the degree of difference amongst the bird communities from different parts of the region (subdivided into 102 UTM squares each covering an area of 100 km2) using the average Euclidean distance (AED) between the various squares which was calculated based on the levels of abundance of the different species. The presence of FH would have implied the following: a tendency of increase of generalist species, a decrease of the specialists, a CSI reduction, a AED reduction. During the period considered it was observed that there was an increase of over half (50.7%) of generalist species, whereas just 23.2% was declining. Amongst the specialists, the declining species were equal to those increased (12.7%). Although there was an increment of the generalist species, the indexes CSI and AED did not show any significant trend (Spearman test). Overall, our findings do not describe the occurrence of a homogenization process in the last decade of the regional bird community as a whole.